Assessing NH300094, a novel dopamine and serotonin receptor modulator with cognitive enhancement property for treating schizophrenia - Feng, Zijin; Hu, Zhijing; Li, Lei; Yu, Minquan; Zhang, Yiting; Jing, Peng; Xu, Xiangqing; Wu, Jinhui; Hu, Yiqiao; Xu, Xiangyang (Frontiers in Pharmacology, 2024)
NH300094 is a novel antipsychotic candidate with highly antagonistic activity against both serotonin and dopamine receptors, demonstrating robust efficacy in animal models of positive, negative, and cognitive symptoms of schizophrenia. In vitro functional assays have indicated that NH300094 is a potent antagonist of 5-HT receptors and dopamine receptors, with higher relative antagonistic activity against 5-HT2A receptor (5-HT2A IC50=0.47 nM) than dopamine receptors (D2L IC50=1.04 nM；D2S IC50=11.71 nM；D3 IC50=31.55 nM). Preclinical results demonstrated that NH300094 is effective in multiple animal models, including dizocilpine (MK-801) induced hyperlocomotion; Apomorphine (APO) induced climbing; Conditioned Avoidance Response (CAR); DOI-induced head twitch; Forced swimming test and Scopolamine induced cognitive impairment model, which is more extensive than Risperidone. Furthermore, the safety window for extrapyramidal side effects of NH300094 is significantly wider than that of Risperidone (For NH300094, mice catalepsy model ED50/ Mice MK-801 model ED50= 104.6-fold; for Risperidone, mice catalepsy model ED50/ Mice MK-801 model ED50= 12.9-fold), which suggests a potentially better clinical safety profile for NH300094. In conclusion, NH300094 is a novel potent serotonin and dopamine receptors modulator, which has good safety profile and therapeutic potential for the treatment of schizophrenia with cognition disorders.